Beginning JBoss Seam - Nusairat, Joseph Faisal (Apress, 2012)
Agile, agile, agile, Ruby, Ruby, Ruby. It seems like every conference you go to these days talks about either agile or Ruby. Those are the big buzzwords in the industry. Everywhere you go, that’s all you seem to hear. And as my friend Rob Stevenson says, that’s all he wants to do. In fact, the only books he reads now are Ruby books. The real question is, why? Personally I think it’s because he likes a limited selection of books. But the other reason is, Ruby is fun. It’s fast, it’s cool, it’s new, and it makes development a pleasure. And computer-savvy developers seem to love anything new. I honestly get a bit tired of everything coming out calling itself agile. Its such a key word these days that I am just waiting for recruiters and sales managers of consulting companies to start telling their clients they need agile developers.